The other side of the mark sheet: lessons learnt when medical students assess peers in formative clinical examinations - Rienits, Helen (Frontiers in Medicine, 2024)
This study aimed to investigate the experience of medical students assessing their cohort peers in formative clinical assessment. The exercise was designed to provide students with a formative experience prior to their summative assessment, and to determine what students could learn by being on the 'other side of the mark sheet'. Students were grateful for the experience learning both from the assessment practice, and from the individual written feedback provided immediately afterwards. They also described how much they learnt from seeing the assessment from the assessor's viewpoint, with many students commenting that they learnt more from being the 'assessor' than from being the 'student' in the process. Students were asked how they felt about being assessed by their peers, with some describing the experience as being more intimidating and stressful than when compared to assessment by clinicians. An interesting aspect of this study is that it also demonstrates some findings which suggest that the students' current learning context appears to have an effect on their attitudes to their peers as assessors. It is possible the competitive cultural milieu of the teaching hospital environment may have a negative effect on medical student collegiality and peer support.